The Role of Gut Microbiota in Mice With Bile Duct Ligation-Evoked Cholestatic Liver Disease-Related Cognitive Dysfunction - Yang, Bowen; Sun, Tianning; Chen, Yingle; Xiang, Hongbing; Xiong, Jun; Bao, Shiting (Frontiers in Microbiology, 2022)
The pathogenesis of Hepatic Encephalopathy (HE) is complex and multifactorial. The development of metagenomics sequencing technology led to show the significant role of gut microbiota in the pathogenesis of cognitive dysfunction, which paved the way for further research in this field. However, it is unknown whether gut microbiota plays a role in bile duct ligation (BDL)-evoked cholestatic liver disease-related cognitive dysfunction induced by. The aim of this investigation is to assess BDL-mice induced cognitive dysfunction and meanwhile to delineate the alteration of gut microbiota in cognitive dysfunction mice, which may underline the role of gut microbiota in BDL-mice induced cognitive dysfunction. Our study was carried out in male C57BL/6J mice with bile duct ligation. The liver functions were assessed via different biochemical markers (ALT, AST, ALP, TBIL, TBA) and a histopathological examination of the liver tissue. We used the novel object recognition test (NORT) to assess cognitive dysfunction, and hierarchical cluster analysis of NORT results was used to classify BDL mice with or without cognitive dysfunction (CD)-like phenotype. Then, 16S ribosomal RNA (rRNA) gene sequencing was used to compare the gut bacterial composition between CD and Non-CD phenotypes in BDL mice. According to our results, we concluded that bile duct ligation can significantly change the gut microbiota composition, and Bacteroides fragilis, Bacteroides ovatus V975 and Bacteroides thetaiotaomicron play a vital role in BDL-evoked cholestatic liver disease-related cognitive dysfunction.